2023
DOI: 10.1186/s13722-023-00386-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based clinicians lack knowledge and comfort in initiating medications for opioid use disorder: opportunities for training innovation

Abstract: Background Hospital-based clinicians infrequently initiate medications for opioid use disorder (MOUD) for hospitalized patients. Our objective was to understand hospital-based clinicians’ knowledge, comfort, attitudes, and motivations regarding MOUD initiation to target quality improvement initiatives. Methods General medicine attending physicians and physician assistants at an academic medical center completed questionnaires eliciting barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Participants reported that processes to screen for, and to diagnose OUD, to initiate medications for OUD, and to ensure OUD treatment linkage following hospital discharge could be improved with protocols or pathways. Thus, we will develop an electronic health record (EHR)-based pathway that incorporates nursing prompts to complete screening questions for unhealthy substance use at hospital admission, an embedded COWS 35 38 To address this barrier, we will offer quarterly in-person or video conferencing seminars with educational content including how to initiate medications for OUD, for example, traditional versus low dose buprenorphine initiation, the legality around the use of medications for OUD in the hospital and outpatient setting, and clear goals and expectations for nurses, clinicians, and social workers to incorporate these OUD treatment pathways into their hospital workflow. We will provide positive feedback to clinicians with updates on success stories of patients who remain engaged in treatment following in-hospital OUD treatment initiation to motivate and enhance practice change.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported that processes to screen for, and to diagnose OUD, to initiate medications for OUD, and to ensure OUD treatment linkage following hospital discharge could be improved with protocols or pathways. Thus, we will develop an electronic health record (EHR)-based pathway that incorporates nursing prompts to complete screening questions for unhealthy substance use at hospital admission, an embedded COWS 35 38 To address this barrier, we will offer quarterly in-person or video conferencing seminars with educational content including how to initiate medications for OUD, for example, traditional versus low dose buprenorphine initiation, the legality around the use of medications for OUD in the hospital and outpatient setting, and clear goals and expectations for nurses, clinicians, and social workers to incorporate these OUD treatment pathways into their hospital workflow. We will provide positive feedback to clinicians with updates on success stories of patients who remain engaged in treatment following in-hospital OUD treatment initiation to motivate and enhance practice change.…”
Section: Discussionmentioning
confidence: 99%
“…Use of these specific medications is associated with increased days of antibiotic therapy, 21 decreased risk of recurrent infection, 22 and reduced overdose mortality 23 among hospitalized patients with infections and OUD, however, hospital clinicians are reluctant to initiate these medications due to a lack of experience and training. 24 In one study of Veterans Affairs hospitals, fewer than 15% of hospitalized patients with OUD were ever treated with these medications. 12 Proposing the use of oxycodone or hydromorphone STERN ET AL.…”
Section: Drug Abusementioning
confidence: 99%
“…7,8 Second, largely due to a lack of knowledge and teaching, many hospital providers are uncomfortable treating SUDs – including opioid use disorder (OUD) and alcohol use disorder (AUD), for which evidence-based treatments are widely available. 4,10,11 Together, these factors likely contribute to an established under-treatment of these SUDs in hospital settings, in addition to lower provider engagement, patient-provider collaboration, and treatment adherence. 1118…”
Section: Introductionmentioning
confidence: 99%
“…4,10,11 Together, these factors likely contribute to an established under-treatment of these SUDs in hospital settings, in addition to lower provider engagement, patient-provider collaboration, and treatment adherence. 1118…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation